Carriage Dynamics of Pneumococcal Serotypes in Naturally Colonized Infants in a Rural African Setting During the First Year of Life - Chaguza, Chrispin; Senghore, Madikay; Bojang, Ebrima; Lo, Stephanie W.; Ebruke, Chinelo; Gladstone, Rebecca A.; Tientcheu, Peggy-Estelle; Bancroft, Rowan E.; Worwui, Archibald; Foster-Nyarko, Ebenezer; Ceesay, Fatima; Okoi, Catherine; et al. (Frontiers in Pediatrics, 2021)
Streptococcus pneumoniae (the pneumococcus) carriage precedes invasive disease and influences population-wide strain dynamics, but limited data exist on temporal carriage patterns of serotypes due to prohibitive costs of longitudinal studies. Here, we report carriage prevalence, duration, clearance and acquisition rates of pneumococcal serotypes sampled from newborn infants bi-weekly from week 1 to 27, and then bi-monthly from week 35 to 52 in the Gambia. We used sweep latex agglutination and whole genome sequencing to serotype the isolates. We show a rapid pneumococcal acquisition with nearly 31% of the infants colonised by the end of first week after birth but quickly reaching over 95% after two months. Co-colonisation with multiple serotypes was consistently observed in over 40% of the infants at each sampling point during the first year of life. Overall, the mean acquisition time and carriage duration regardless of serotype was 38 and 24 days respectively but varied considerably between serotypes comparable to observations from other regions. Our data will inform disease prevention and control measures including providing baseline data for parameterising infectious disease mathematical models including those assessing the impact of clinical interventions such as pneumococcal conjugate vaccines.